Analytical and Experimental Analysis of Periodic Oscillations in a Nonlinear Temperature Control System - Yu, Bo (Journal of Vibration Testing and System Dynamics, 2026)
This research studies the periodic temperature oscillations of a temperature control system. The nonlinear differential equation of a micro-controller-based temperature control system is derived using the energy balance method. The system parameters are optimized based on the experimental data. The method of implicit mapping is introduced. Through this mapping structures of periodic temperature responses, the analytical solutions of the steady-state temperature oscillations are computed which can be used to predict the experimental response. From the results of the implicit mapping, the amplitude curves of the Fourier series are calculated. Finally, the comparisons of the numerical, analytical, and experimental results are presented.